Methionine Sulfoxide Reductase A (MsrA) Deficient Mycoplasma genitalium Shows Decreased Interactions with Host Cells - Das, Kishore (Public Library of Science, 2012)
Mycoplasma genitalium is an important sexually transmitted pathogen that affects both men and women. In genital-mucosal tissues, it initiates colonization of epithelial cells by attaching itself to host cells via several identified bacterial ligands and host cell surface receptors. We have previously shown that a mutant form of M. genitalium lacking methionine sulfoxide reductase A (MsrA), an antioxidant enzyme which converts oxidized methionine (Met(O)) into methionine (Met), shows decreased viability in infected animals. To gain more insights into the mechanisms by which MsrA controls M. genitalium virulence, we compared the wild-type M. genitalium strain (G37) with an msrA mutant (MS5) strain for their ability to interact with target cervical epithelial cell lines (HeLa and C33A) and THP-1 monocytic cells. Infection of epithelial cell lines with both strains revealed that MS5 was less cytotoxic to HeLa and C33A cell lines than the G37 strain. Also, the MS5 strain was more susceptible to phagocytosis by THP-1 cells than wild type strain (G37). Further, MS5 was less able to induce aggregation and differentiation in THP-1 cells than the wild type strain, as determined by carboxyfluorescein diacetate succinimidyl ester (CFSE) labeling of the cells, followed by counting of cells attached to the culture dish using image analysis. Finally, MS5 was observed to induce less proinflammatory cytokine TNF-α by THP-1 cells than wild type G37 strain. These results indicate that MsrA affects the virulence properties of M. genitalium by modulating its interaction with host cells.